2013
DOI: 10.4103/0019-557x.115003
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality among the neonates transported to referral centre in Delhi, India

Abstract: A descriptive study was conducted with an objective to determine the predictors of mortality among referred neonates and to ascertain their transport characteristics. A total of 300 consecutive neonates who were transferred to the centre were enrolled in the study. Following information were recorded: maternal details, birth details, interventions before transportation, details of transportation and neonatal condition at arrival. Detailed clinical assessment and management was done as per standard neonatal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
55
3
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 4 publications
15
55
3
14
Order By: Relevance
“…A K Saha in his study had only 22% mortality associated with septicaemia (16) . This higher rate of mortality in our study could be due to the fact that our hospital is the only referral centre for paediatric surgery in the state of Rajasthan, hence the delay in starting the initial treatment, transportation time and other undiagnosed metabolic derangements as shown by Narang M et al in his study done at a tertiary centre in Delhi (18) . He states that extreme low birth weight (<1kg) and transportation time more than 1hr were significant predictors of mortality.Babies delivered outside the hospital need to travel several hours to get to a specialist hospital that offers neonatal surgical services during which time the baby's condition may deteriorate, leading to increased operative risk and mortality.…”
Section: Discussionmentioning
confidence: 63%
“…A K Saha in his study had only 22% mortality associated with septicaemia (16) . This higher rate of mortality in our study could be due to the fact that our hospital is the only referral centre for paediatric surgery in the state of Rajasthan, hence the delay in starting the initial treatment, transportation time and other undiagnosed metabolic derangements as shown by Narang M et al in his study done at a tertiary centre in Delhi (18) . He states that extreme low birth weight (<1kg) and transportation time more than 1hr were significant predictors of mortality.Babies delivered outside the hospital need to travel several hours to get to a specialist hospital that offers neonatal surgical services during which time the baby's condition may deteriorate, leading to increased operative risk and mortality.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, antenatally very few cases were detected as a result of ignorance and non availability of proper antenatal services in the periphery. An Indian study proved that prolonged neonatal transport (>1 hour) was found to increase the mortality among transported neonates [18].…”
Section: Discussionmentioning
confidence: 99%
“…Dans l'EDS continue de 2014 du Sénégal, le pourcentage de naissances à domicile pour la région de Dakar était plus faible à 4,4 % [2]. Dans une série indienne, près de 25 % des nouveau-nés transférés étaient nés à domicile [13]. Ces naissances à domicile, sans assistance médicale, sont des sources potentielles de complications maternonéonatales dans nos pays [2].…”
Section: Contexte Obstétricalunclassified
“…Les autres motifs de transfert néonatal retrouvés dans la littérature et dans notre étude sont : détresse respiratoire, asphyxie périnatale, macrosomie foetale, présentations anormales, ictère, distension abdominale [11][12][13].…”
Section: Motifs De Transfertunclassified